Quality of life in chronic venous disease women - Dalton de Lima-Junior; Ozeas Lins-Filho; Jessica da Silva; Giselly Leite; Luana Gusmão; Daniela Karina da Silva Ferreira (Revista Brasileira de Atividade Física e Saúde)
The aim of the study was to verify the relationship between physical function and quality of life in women with chronic venous disease. Physical function was evaluated by the tests: chair stand test (lower limbs strength), arm curl (upper limbs strength), 6-minute walk (aerobic fitness), back scratch (upper limbs flexibility), sit and reach (lower limbs flexibility), and time up-and-go (agility). Quality of life was assessed by e World Health Organization Quality of Life-BREF (WHOQOL-BREF) questionnaire, which is composed by physical, psychologic, social, environmental, and global domains. For statistical analysis, the Pearson correlation coefficient was used with an alpha of 5%. Patients evaluated were 32 (61.27 ± 7.78 years). A significant correlation was observed between the physical domain of quality of life with the chair stand test (r = 0.46; p = 0.001), arm curl (r = 0.39, p = 0.002), and 6-minute walk test (r = 0.45; p = 0.001). Also, chair stand test presented low correlation with global quality of life (r = 0.36, p = 0.004). The physical domain of quality of life measured by the WHOQOL-BREF questionnaire is related to lower and upper limbs strength and physical fitness in women with chronic venous disease but presented weak correlation with the global domain of quality of life. Thus, in women with CVD, the muscular strength of lower and upper limbs, and physical fitness is correlated with the physical domain of quality of life.